Resistencia a la fractura de los postes de fibra de vidrio y colados, utilizados en dientes anteriores tratados endodónticamente. Revisión bibliográfica - Ordoñez Carchi, Wilson David (2022)
We usually rehabilitate endodontically treated anterior teeth with intra-radicular posts that serve as a bonding element between the root and coronal portion of the tooth. These posts can be cast and prefabricated; to go deeper into the subject, we evaluated the fracture resistance of fiberglass and cast poles in endodontically treated anterior teeth employing a literature review. For its development, we took into consideration25 scientific articles in English and Spanish with a maximum age range of 10 years, published in different scientific databases: Pubmed, Google Scholar, and Elsevier. The results show that the 17 fiberglass poles obtained a maximum flexural resistance of 9001.9 MPa and a minimum of 1213.2 MPa; Unlike the cast posts made from different alloys and represented in 17 samples, the nickel-chromium post reached a maximum flexural resistance of 14642.02 MPa, the gold posts obtained 9,491.22 MPa, and the Titanium 3,816.49. MPa and the titanium posts was 3753.73 MPa. When compared with the fiberglass poles, which have attained a maximum resistance of 9001.9 MPa. In conclusion, the fiberglass and cast posts comply with the flexural strength established by ISO 10477 and 22674 as corresponds. However, we considered that in the rehabilitation with intra-radicular posts of endodontically restored anterior teeth, the fiberglass posts would be indicated since they have good flexural strength and a modulus of elasticity (24 to 40 GPa) similar to dentin (20 GPa), minimizing the risk of fracture